Net primary productivity and its partitioning in response to precipitation gradient in an alpine meadow. Issue 1 (December 2017) - Zhang, Fangyue; Quan, Quan; Song, Bing; Sun, Jian; Chen, Youjun; Zhou, Qingping; Niu, Shuli
Abstract The dynamics of net primary productivity (NPP) and its partitioning to the aboveground versus belowground are of fundamental importance to understand carbon cycling and its feedback to climate change. However, the responses of NPP and its partitioning to precipitation gradient are poorly understood. We conducted a manipulative field experiment with six precipitation treatments (1/12 P, 1/4 P, 1/2 P, 3/4 P, P, and 5/4 P, P is annual precipitation) in an alpine meadow to examine aboveground and belowground NPP (ANPP and BNPP) in response to precipitation gradient in 2015 and 2016. We found that changes in precipitation had no significant impact on ANPP or belowground biomass in 2015. Compared with control, only the extremely drought treatment (1/12 P) significantly reduced ANPP by 37.68% and increased BNPP at the depth of 20–40 cm by 80.59% in 2016. Across the gradient, ANPP showed a nonlinear response to precipitation amount in 2016. Neither BNPP nor NPP had significant relationship with precipitation changes. The variance in ANPP were mostly due to forbs production, which was ultimately caused by altering soil water content and soil inorganic nitrogen concentration. The nonlinear precipitation-ANPP relationship indicates that future precipitation changes especially extreme drought will dramatically decrease ANPP and push this ecosystem beyond threshold.